Aromatic Cytokinin Arabinosides Promote PAMP-like Responses and Positively Regulate Leaf Longevity - Bryksová, Magdaléna; Dabravolski, Siarhei; Kučerová, Zuzana; Zavadil Kokáš, Filip; Špundová, Martina; Plíhalová, Lucie; Takáč, Tomáš; Grúz, Jiří; Hudeček, Martin; Hloušková, Veronika; Koprna, Radoslav; Novák, Ondřej; et al. (ACS chemical biology, 2020)
Cytokinins are plant hormones with biological functions ranging from coordination of plant growth to the regulation of biotic and abiotic stress-related responses and senescence. The components of the plant immune system can learn from past elicitations by microbial pathogens and herbivores and adapt to new threats. It is known that plants can enter the primed state of enhanced defense induced by either natural or synthetic compounds. While the involvement of cytokinins in defense priming has been documented, no comprehensive model of their action has been provided to date. Here, we report the functional characterization of two aromatic cytokinin derivatives, 6-benzylaminopurine-9-arabinosides (BAPAs), 3-methoxy-BAPA and 3-hydroxy-BAPA, that proved to be effective in delaying senescence in detached leaves while having low interactions with the cytokinin pathway. An RNA-seq profiling study on Arabidopsis leaves treated with 3-methoxy-BAPA revealed that short and extended treatments with this compound shifted the transcriptional response markedly toward defense. Both treatments revealed upregulation of genes involved in processes associated with plant innate immunity such as cell wall remodeling and upregulation of specific MAP kinases, most importantly MPK11, which is a MAPK module involved in stress-related signaling during the pathogen-associated molecular patterns (PAMPs) response. In addition, elevated levels of JA and its metabolites, jasmonate/ethylene-driven upregulation of PLANT DEFENSIN 1.2 (PDF1.2) and other defensins, and also temporarily elevated levels of reactive oxygen species marked the plant response to 3-methoxy-BAPA treatment. Synergistic interactions were observed when plants were cotreated with 3-hydroxy-BAPA and the flagellin-derived bacterial PAMP peptide (flg22), leading to the enhanced expression of the PAMP-triggered immunity (PTI) marker gene FRK1. Our data collectively show that some BAPAs can sensitively prime the PTI responses in a low micromolar range of concentrations while having no observable negative effects on the overall fitness of the plant.
Keywords: Gene Expression Regulation, Plant; imunita rostlin; vztahy mezi strukturou a aktivitou; arabinonukleosidy; MAP kinasový signální systém; mitogenem aktivované proteinkinasy; Arabidopsis; Cytokinins; Plant Immunity; molekulární struktura; PAMP struktury; Pathogen-Associated Molecular Pattern Molecules; Plant Leaves; Mitogen-Activated Protein Kinases; regulace genové exprese u rostlin; Molecular Structure; Structure-Activity Relationship; Arabidopsis Proteins; cytokininy; listy rostlin; MAP Kinase Signaling System; Arabinonucleosides; proteiny huseníčku